Publication Patterns and the Evolution of the Dynamic Capabilities Concept in Global Business Literature - Judijanto, Loso; Suroso, Adi (The Eastasouth Management and Business, 2025)
This study examines the evolution, structure, and global dissemination of the dynamic capabilities (DC) concept within business and management literature through a comprehensive bibliometric analysis using VOSviewer. Drawing on data from the Scopus database covering the period 1997–2024, the study maps co-citation relationships, keyword co-occurrence, country collaboration patterns, and thematic trends. The results reveal that Teece, D.J. remains the most influential author, anchoring the field’s theoretical development, while emerging scholars—especially from China and India—are contributing to its expansion. The United States leads international collaboration networks, followed by the United Kingdom and China. Thematic mapping indicates a core cluster focused on innovation, knowledge management, and enterprise resource management, while new clusters highlight intersections with artificial intelligence, machine learning, and sustainability. Temporal analysis shows a shift from system-based approaches toward digitally enabled and strategically integrated research. These findings demonstrate the growing interdisciplinarity, global reach, and strategic relevance of dynamic capabilities, providing valuable insights for scholars and practitioners seeking to navigate organizational adaptation in a rapidly changing business environment.